1994
DOI: 10.1017/s0022112094003101
|View full text |Cite
|
Sign up to set email alerts
|

A study of streamwise vortex structure in a stratified shear layer

Abstract: The existence of an organized streamwise vortical structure, which is superimposed on the well known coherent spanwise vorticity in nominally two-dimensional free shear layers, has been studied extensively. In the presence of stratification, however, buoyancy forces contribute to an additional mechanism for the generation of streamwise vorticity. As the spanwise vorticity layer rolls up and pulls high-density fluid above low-density fluid, a local instability results. The purpose of the current investigation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
45
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 21 publications
11
45
0
Order By: Relevance
“…At P r = 1, the density structure of the billow has been mainly destroyed by diffusion at t * 2 . The highly structured density field of the P r = 700 billow resembles the density field of the billows observed in the experiments of Schowalter et al (1994) with P r ∼ 1500 and Atsavapranee and Gharib (1997) with P r ∼ 600, where the billow consists of layers of rolling fluid with very sharp interfaces. At P r = 700, very fine structures have formed, with very little diffusion.…”
Section: Two and Three-dimensional Evolution Of Kh Billowssupporting
confidence: 66%
“…At P r = 1, the density structure of the billow has been mainly destroyed by diffusion at t * 2 . The highly structured density field of the P r = 700 billow resembles the density field of the billows observed in the experiments of Schowalter et al (1994) with P r ∼ 1500 and Atsavapranee and Gharib (1997) with P r ∼ 600, where the billow consists of layers of rolling fluid with very sharp interfaces. At P r = 700, very fine structures have formed, with very little diffusion.…”
Section: Two and Three-dimensional Evolution Of Kh Billowssupporting
confidence: 66%
“…Recent investigations of Kelvin‐Helmholtz instability have found that the transition to turbulence involves vortices that are elongated along the direction of shear and wrap around the overturning billows. This was originally anticipated by Klaassen and Peltier [1985b], and has since been demonstrated in both the laboratory [ Thorpe , 1985; Showalter et al , 1994] and numerical simulations [e.g., Palmer et al , 1996]. We would expect to see this process manifested in the airborne measurements as three‐dimensional motion developing along the direction of shear, initially as coherent oscillations of the cross‐shear component of the wind.…”
Section: Discussionmentioning
confidence: 56%
“…parallel to the front). Using a stratified-mixing-layer analogue, Parsons (1998) noticed a similarity to the Klaasen-Peltier instability observed in stratifiedmixing layers (Schowalter et al, 1994). The KlaasenPeltier instability occurs when dense fluid is forced over light fluid by the Kelvin-Helmholtz instability in a stratified flow (Klaasen & Peltier, 1985).…”
Section: Frontal Dynamicsmentioning
confidence: 93%